2021
DOI: 10.1021/acsami.0c19239
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Assembly of Atomically Precise Metal Clusters as a Luminescent Strain Sensor

Abstract: We demonstrate the formation of a versatile luminescent organo-inorganic layered hybrid material, composed of bovine serum albumin (BSA)-protected Au30 clusters and aminoclay sheets. X-ray diffraction revealed the intercalation of Au30@BSA in the layered superstructure of aminoclay sheets. Coulombic attraction of the clusters and the clay initiates the interaction, and the appropriate size of the clusters allowed them to intercalate within the lamellar aminoclay galleries. Electron microscopy measurements conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…14 c The gel displayed a reversible change of the emission intensity upon deformation to 300% strain by the reorganization of pyrene. 14 c More recently, it was reported that a film consisting of bovine serum albumin (BSA)@Au 30 clusters intercalated in an “aminoclay”, which is a layered silicate with aminopropyl groups exposed on the surface, and poly(vinyl alcohol) (PVA), 15 exhibited a mechanochromic response from red to white upon stretching at 300% strain. The mechanochromism was explained by the structural distortion of the clusters confined within the aminoclay.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14 c The gel displayed a reversible change of the emission intensity upon deformation to 300% strain by the reorganization of pyrene. 14 c More recently, it was reported that a film consisting of bovine serum albumin (BSA)@Au 30 clusters intercalated in an “aminoclay”, which is a layered silicate with aminopropyl groups exposed on the surface, and poly(vinyl alcohol) (PVA), 15 exhibited a mechanochromic response from red to white upon stretching at 300% strain. The mechanochromism was explained by the structural distortion of the clusters confined within the aminoclay.…”
mentioning
confidence: 99%
“…The mechanochromism was explained by the structural distortion of the clusters confined within the aminoclay. 15…”
mentioning
confidence: 99%
“…This favors the formation of a Au 30 core inside a BSA molecule. This cluster was previously reported and studied with different techniques. ,, We followed the same ratio of metal ion/protein concentration during electrospray synthesis. As a result, the Au 30 core was formed.…”
Section: Resultsmentioning
confidence: 99%
“…Two examples are to be mentioned. (1) By using C 58 fullerenes as perfect mono-sized building blocks, micrometer-thick films have been formed on inert surfaces and subsequently, their mechanical properties have been measured [199]; (2) a nano-inorganic layered hybrid material, composed of bovine serum albumin (BSA)-protected atomically precise Au 30 clusters and aminoclay sheets was synthesized and its luminescence properties were studied and applied in a strain sensor [200]. The availability of well-defined clusters in sufficient quantities opens up opportunities for the design of novel materials structures, as will be described in the following paragraphs.…”
Section: Cluster and Nanoparticle Assembly Towards Architectured Materialsmentioning
confidence: 99%